A Systematic Review and Meta-Analysis of Retinal Microvascular Features in Alzheimer's Disease - Jin, Qifang; Lei, Yiming; Wang, Ruoxin; Wu, Huiying; Ji, Kaibao; Ling, Ling (Frontiers in Aging Neuroscience, 2021)
Objective: The aim of this meta-analysis was to investigate retinal microvascular features in patients with Alzheimer's disease (AD) using optical coherence tomography angiography (OCTA). Methods: PubMed, Cochrane Library, Embase, and Web of Science databases were systematically searched for published articles comparing retinal microvascular characteristics in subjects with AD and controls. The mean difference (MD) with a 95% confidence interval (CI) was used to assess continuous variables. Review Manager Version (RevMan) 5.30, was employed to analyze the data. Results: Nine studies were included in the meta-analysis. The analysis revealed that the macular whole enface superficial and deep vessel density (VD) values measured by OCTA were significantly lower in patients with AD than in controls (MD = −1.10, P < 0.0001; MD = −1.61, P = 0.0001, respectively). The value measured by OCTA for parafoveal superficial VD in patients with AD was also remarkably lower than that in the control group (MD = −1.42, P = 0.001), whereas there was no significant difference in the value for parafoveal deep VD (MD = −3.67, P = 0.19), compared to the controls. In addition, the foveal avascular zone (FAZ) was larger in patients with AD than in the control group (MD = 0.08, P = 0.07), although it did not reach statistical significance. Conclusions: The present meta-analysis indicated that the macular whole enface and parafoveal vessel densities were reduced in patients with AD. Moreover, our pooled data revealed that FAZ is larger in patients with AD. Consequently, OCTA may be utilized as a diagnostic tool to identify and monitor patients with AD.